Analysis of tripartite motif (TRIM) family gene expression in prostate cancer bone metastases. (6th September 2021) - Offermann, Anne; Kang, Duan; Watermann, Christian; Weingart, Anika; Hupe, Marie C; Saraji, Alireza; Stegmann-Frehse, Janine; Kruper, Rosemarie; Schüle, Roland; Pantel, Klaus; Taubert, Helge; Duensing, Stefan; et al.
Abstract: Tripartite motif (TRIM) family proteins are post-translational protein modifiers with E3-ubiquitin ligase activity, thereby involved in various biological processes. The molecular mechanisms driving prostate cancer (PCa) bone metastasis (BM) are incompletely understood, and targetable genetic alterations are lacking in the majority of cases. Therefore, we aimed to explore the expression and potential functional relevance of 71 TRIM members in bone metastatic PCa. We performed transcriptome analysis of all human TRIM family members and 770 cancer-related genes in 29 localized PCa and 30 PCa BM using Nanostring. KEGG, STRING and Ubibrowser were used for further bioinformatic gene correlation and pathway enrichment analyses. Compared to localized tumors, six TRIMs are under-expressed while nine TRIMs are over-expressed in BM. The differentially expressed TRIM proteins are linked to TNF-, TGFβ-, PI3K/AKT- and HIF-1-signaling, and to features such as proteoglycans, platelet activation, adhesion and ECM-interaction based on correlation to cancer-related genes. The identification of TRIM-specific E3-ligase-substrates revealed insight into functional connections to oncogenes, tumor suppressors and cancer-related pathways including androgen receptor- and TGFβ signaling, cell cycle regulation and splicing. In summary, this is the first study that comprehensively and systematically characterizes the expression of all TRIM members in PCa BM. Our results describe post-translational protein modification as an important regulatory mechanism of oncogenes, tumor suppressors, and pathway molecules in PCa progression. Therefore, this study may provide evidence for novel therapeutic targets, in particular for the treatment or prevention of BM. Abstract : Post-translational protein modification has a major impact on oncogenic signaling. Here, we provide a comprehensive network linking cancer-related genes to the E3-ubiquitin ligases tripartite motif family proteins in prostate cancer bone metastases.